The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pr8050577
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Supply Chain Agility to Foster Sustainability: Fuzzy-DSS for a Saudi Manufacturing Organization

Abstract: Supply chain agility and sustainability is an essential element for the long-term survival and success of a manufacturing organization. Agility is an organization’s ability to respond rapidly to customers’ dynamic demands and volatile market changes. In a dynamic business environment, manufacturing firms demand agility to be evaluated to support any alarming decision. Sustainability is an aspect to sustain collaboration, value creation, and survival of firms under a dynamic competitive business scenario. Agili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…That is, there is a positive and significant influence of supply chain agility on the sustainability of supply chain performance, this provides evidence that H2 in this study is accepted. The results of this study are also supported by previous research found that supply chain agility has a positive effect on the sustainability of the supply chain performance (Nath & Agrawal, 2020;Perera et al, 2014;Rehman et al, 2020). The results of this study found that furniture SMEs that can quickly run their operational processes will be superior to their competitors, and this can have an impact on the sustainability of supply chain performance in the future.…”
Section: The Effect Of Supply Chain Agility On the Supply Chain Performance Sustainabilitysupporting
confidence: 86%
See 2 more Smart Citations
“…That is, there is a positive and significant influence of supply chain agility on the sustainability of supply chain performance, this provides evidence that H2 in this study is accepted. The results of this study are also supported by previous research found that supply chain agility has a positive effect on the sustainability of the supply chain performance (Nath & Agrawal, 2020;Perera et al, 2014;Rehman et al, 2020). The results of this study found that furniture SMEs that can quickly run their operational processes will be superior to their competitors, and this can have an impact on the sustainability of supply chain performance in the future.…”
Section: The Effect Of Supply Chain Agility On the Supply Chain Performance Sustainabilitysupporting
confidence: 86%
“…In a dynamic business environment, the furniture industry demands supply chain agility be evaluated to support any worrisome decisions in the midst of a pandemic or post-pandemic because agility is an ability that encourages competitiveness to foster sustainability aspects. Several previous studies have also shown the influence of supply chain agility on the sustainability of supply chain performance (Nath & Agrawal, 2020;Perera et al, 2014;Rehman et al, 2020). Predicated on the explanation above, this study has a necessary purpose to examine and review "the role of supply chain agility in influencing the sustainability of supply chain performance and supply chain resilience".…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The rapid industrialization lays the foundation for the emergence of new innovative methods and tools like agile manufacturing (Lokhande and Sarode, 2020). Agile manufacturing is best suitable for the market situations with product characteristics like high variety, small volume, short life cycle, product specification–based competition and higher profit margins (Rehman et al , 2020). Agile manufacturing is not about small-scale continuous improvements but an entirely different way of doing business (Kidd, 1994; Gunasekaran, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agility encourages competitiveness to cultivate sustainability (Rehman et al , 2020). Shekarian et al (2020) suggested internal and external integration with potential suppliers and customers as the key predecessors to achieve agility.…”
Section: Literature Reviewmentioning
confidence: 99%